2014
DOI: 10.1016/j.compedu.2013.09.017
|View full text |Cite
|
Sign up to set email alerts
|

The cognitive impact of interactive design features for learning complex materials in medical education

Abstract: To identify the most effective way for medical students to interact with a browser-based learning module on the symptoms and neurological underpinnings of stroke syndromes, this study manipulated the way in which subjects interacted with a graphical model of the brain and examined the impact of functional changes on learning outcomes. It was hypothesized that behavioral interactions that were behaviorally more engaging and which required deeper consideration of the model would result in heightened cognitive in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 41 publications
1
45
0
1
Order By: Relevance
“…These elements range from basic user controls that allow an influence over the presentation of instructional slides (e.g., Tabbers & de Koeijer, 2010) to immersive digitally‐enhanced environments (e.g., Johnson‐Glenberg, Megowan‐Romanowicz, Birchfield, & Savio‐Ramos, 2016). However, the literature on interactivity also contains negative results, as there are instances in which more static forms of learning media have resulted in better learning performance than versions that incorporated features such as user controls or related forms of responsive interfaces (e.g., Song et al, 2014). Results such as these have been explained in reference to an assumed cognitive overload (e.g., Skulmowski, Pradel, Kühnert, Brunnett, & Rey, 2016).…”
mentioning
confidence: 99%
“…These elements range from basic user controls that allow an influence over the presentation of instructional slides (e.g., Tabbers & de Koeijer, 2010) to immersive digitally‐enhanced environments (e.g., Johnson‐Glenberg, Megowan‐Romanowicz, Birchfield, & Savio‐Ramos, 2016). However, the literature on interactivity also contains negative results, as there are instances in which more static forms of learning media have resulted in better learning performance than versions that incorporated features such as user controls or related forms of responsive interfaces (e.g., Song et al, 2014). Results such as these have been explained in reference to an assumed cognitive overload (e.g., Skulmowski, Pradel, Kühnert, Brunnett, & Rey, 2016).…”
mentioning
confidence: 99%
“…The influence spatial proximity has on learning was explored in multiple studies. 12,[15][16][17][18][19] A study 15 using first-year physical therapy students found that by physically integrating written text into figures there was a significant reduction in mental effort and improved retention of information compared to traditional photographs with written text referring to them. Consequently, when students are required to search for segments of written text and labels for pictures, a spilt-attention effect occurs, which increases cognitive load.…”
Section: Researchmentioning
confidence: 99%
“…These results indicate that attention-guided cueing allows for the processing of complex information more effectively by freeing space in working memory. Another study 18 exposed medical students to information on stroke conditions in 4 different formats, all consisting of browser-based learning and differing in level of cognitive and behavioral activity. The formats included observing a video that was learner-paced, sliding a handle below a model to move an embolus, clicking on vascular structures, and dragging the embolus along a path of arteries.…”
Section: Researchmentioning
confidence: 99%
“…In the former case, lack of possibilities can make exploratory activities ineffective and inefficient, even frustrating. In the latter case, some costs might be related to time consumption and increased cognitive demand [28,[31][32][33][34][35], as users might need to spend time testing all available interactions, figuring out their functions and benefits, and remembering how and when to use them. The challenge of designing complementary interactions is to balance the need to provide interactions that are conjunctively supportive, yet do not impose additional unintended load on users.…”
Section: Complementary Interactionsmentioning
confidence: 99%